Study of land dynamics in Benin: case of the municipality of Allada - DEGBEGNON, LÉOPOLD; CODJO, Ezéchias (My University, 2018)
The present study on land dynamics from GIS tools and remote sensing was conducted in the municipality of Allada in southern Benin. The objective is to show the evolution of the habitats according to the population growth and its land situation in relation to the various urbanization operations on the horizon 2050. The methodological approach adopted focuses on documentary research, socio-land survey and diachronic cartography based on satellite imagery of 1986, 2000 and 2016 and SIG. From a survey carried out with Idrisi Selva software, the directions of spreading at the horizon 2050 were determined. From 1986 to 2016 the population of the Commune increased from 62880 to 176735 while the area occupied by the habitats increased from 409.87ha to 1008.36ha. Five areas to be developed as a priority have been defined.
Keywords: land dynamics; demography; sprawl habitats; Allada; SIG; Idrisi Selva.